Implementasi Projek Uji Berkala Kendaraan Angkutan Umum Dalam Meningkatkan Kualitas Udara Di Kota Medan - Annisa Sanny; Abri Montgomery Blackstone; Rudi Kristian P.M (Professional: Jurnal Komunikasi dan Administrasi Publik, 2022)
The results of this study have not gone well. This is due to the inability of the Medan City Transportation Service to provide strict sanctions so that there are still people (public transport drivers) who do not periodically test their vehicles. along 245.1 KM which causes a lack of supervision at every point in Medan City.